Metode Penyembuhan Sufi dalam Pengobatan Gangguan Kecemasan : Perspektif Budaya dan Spiritual - Ashari, Ibnu Rasyid; Khodijah, Khodijah (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2025)
Anxiety disorders are one of the most common mental health problems experienced by people around the world. While conventional medical treatments such as cognitive behavioural therapy (CBT) and medications are widely used, these approaches are often inadequate for individuals seeking holistic healing that includes spiritual aspects. Sufi healing methods, rooted in the Islamic mystical tradition, offer an alternative approach that focuses on meditation, dhikr (repetition of God's name), and cleansing of the soul (tazkiyatun nafs), with the aim of achieving emotional balance and inner calm. This article explores the cultural adaptation of Sufi healing methods in the treatment of anxiety disorders in modern society. The research utilises a qualitative approach through a literature review method on how anxiety disorders can be addressed by Sufi healing methods. In addition, a literature review was also conducted to understand the basic principles of the Sufi approach and how they can be applied more universally.